Evaluation of renal osteodystrophy in patients under hemodialysis treatment using digital radiography - Talaeipour AR; Mohammadian Gh; Ghoudarzi D (Tehran University of Medical Sciences, 2001)
Osteodystrophy is one of the most common complications at the last stage of renal disease,"nwhich cause low bone mineral density (BMD) and skeletal deformities in patients. In this study"nevaluation of renal osteodystrophy was evaluated through BMD measurement of 45 under dialysis and"n78 healthy persons by intra-oral digital radiography (RVG). Results Showed that:"n1- The average of BMD in hemodialysis patients was indeed lower than normal population (P^O.OOO)."n2- The mean of BMD of females was lower than males (P=0.021)."n3- There was no correlation between and BMD (P=0.560)."n4- Age and BMD had no significant relationship (P=0.648)."n5- There was negative correlation between alkaline and BMD therefore ALP is a useful predictive factor forBMD(P=0.002).